Analysis of robustness of the Chinese economy and energy supply/demand fluctuations. (28th February 2019) - Mortazavi, Seyed Mostafa; Maleki, Akbar; Yousefi, Hossein
Abstract: Many countries around the world are highly dependent on fossil fuels to supply their energy needs, and price fluctuations of these energy sources have different economic effects on energy importer and exporter countries. Stability of energy and energy security are important subjects for researchers and policy makers. This study considers the effects of energy changes on different economic sectors in China. First, the impact of oil price fluctuations on macro-economic parameters is discussed. Then, the main issues related to energy economics including resilience of the energy sector, energy policies, economic analysis of the energy sector and the electricity market are discussed. Finally, using elasticity measurements, it is estimated that energy consumption in 2020 will increase by 200% compared to 2015, reaching 3358.18 (kg of oil equivalent per capita), as a result of increasing population in China.